Α‐Fe2O3 Film with Highly Photoactivity for Non‐enzymatic Photoelectrochemical Detection of Glucose. Issue 9 (2nd July 2019) - Liu, Fuyan; Wang, Peng; Zhang, Qianqian; Wang, Zeyan; Liu, Yuanyuan; Zheng, Zhaoke; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying; Huang, Baibiao
Abstract: A non‐enzyme photoelectrochemical (PEC) glucose sensor based on α‐Fe2 O3 film is investigated. The α‐Fe2 O3 film was fabricated via a simple spin coating method. The proposed glucose sensor exhibits good selectivity, a fast response time of <5 s, a linear range of 0.05 to 6.0 mM, sensitivity of 17.23 μA mM −1  cm −2 and a detection limit of 0.05 μM. Meanwhile, the excellent performances of the α‐Fe2 O3 sensor were obtained in reproducibility and the long‐term stability under ambient condition. The linear amperometric response of the sensor covers the glucose levels in physiological and clinical for diabetic patients. Therefore, this non‐enzyme PEC sensor based on α‐Fe2 O3 film has a great potential application in the development of glucose sensors. Abstract :